STATUS PERKEMBANGAN DAN IDENTITAS DIRI REMAJA DI SMP NEGERI 49 KRAMAT JATI JAKARTA TIMUR - Pertiwi, Harizza; Zakiyah, Zakiyah; Sutandi, Aan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Adolescence is a period of change in biological, psychological, and social aspects from childhood to adulthood. At this range of time, these changes can affect the development process and identity formation. This process may start at the early stage of adolescence which is in the age of junior high school. If adolescent developmental and identity status are not robust, adolescents tend to be easily exposed to negative behavior such as drug abuse and free sex. The purpose of this study was to determine the status of development and identity of adolescents in SMP Negeri 49 East Jakarta. The method used was descriptive quantitative to describe or to give illustration of the object being studied. Number of respondents was 21 adolescence which attained by calculation using purposive sampling technique. The results obtained are that most respondents have achieved optimal development (85,7%) and more than half of respondents have active identity (57,1%). From these results, it can be seen that not all respondents have achieved optimal development, and there are still many whose identities are less active. This is a natural phenomenon since the development and identity are still in process throughout adolescence until the age of eighteen. Furthermore, it can be concluded that the optimization of development achievement and adolescent self-identity is still needed, for this reason, efforts to promote adolescent health can be carried out both in schools and in the community setting.